2022
DOI: 10.3389/fcvm.2022.887705
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy-Induced Cardiotoxicity: The Role of Multimodality Cardiovascular Imaging

Abstract: Radiotherapy (RT) is one of the pillars of cancer therapy. High-dose radiation exposure on the thorax is mainly used in the context of adjuvant RT after breast surgery, in lung and esophageal cancer, and as a complement to systemic treatment in lymphoma. Due to the anatomical proximity, the heart inevitably receives some radiation that can result in acute and chronic cardiotoxicity, leading to heart failure, coronary artery disease, pericardial and valvular heart disease. Current evidence suggests there is no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 104 publications
0
12
0
1
Order By: Relevance
“…Left ventricular ejection fraction (LVEF) has diagnostic and prognostic meaning for cancer patients, and with advancement, in 3D echocardiography, there is a more precise estimation of its value. Strain echocardiographic imaging is useful for the detection of preclinical adverse effects even before structural heart disease exists [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Left ventricular ejection fraction (LVEF) has diagnostic and prognostic meaning for cancer patients, and with advancement, in 3D echocardiography, there is a more precise estimation of its value. Strain echocardiographic imaging is useful for the detection of preclinical adverse effects even before structural heart disease exists [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear cardiology is a powerful diagnostic tool helping everyday clinical practice detect of toxic effects of radiation treatment. SPECT and PET are very useful for the detection of coronary artery disease, but also heart failure and pericardial syndrome cases [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, measuring specific biomarkers in BC patients' serum during or after RT could contribute to the prediction, diagnosis, and risk assessment of cardiovascular disease [40].Studies have shown that the appropriate biomarkers in patients undergoing RT include cardiac troponin T (cTnT), cardiac troponin I, and natriuretic peptides such as B-type natriuretic peptide (BNP) and N-terminal pro B-type natriuretic peptide (NT-proBNP) (cTnI). Elevated levels of these molecules may indicate increased myocardial stretch and thus may be used as biomarkers for left ventricular dysfunction and heart failure [41,42]. Although such biomarkers are insufficient on their own to determine the path of treatment for each patient, they should be used as a trigger or follow-up tool for the attending physician [43].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of RIHD in patients with NSCLC has emerged as a topic of interest [ 27 ]. Previous studies have investigated the risk of cardiac toxicity and the effect of the cardiac radiation dose on survival in patients with NSCLC [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%